The potential of satellite imagery in soil compaction studies for implementation of precision farming - Norasmanizan Abdullah (School of Environmental Engineering, 2013)
The objective of this study is to evaluate the potential of satellite imagery and GIS (Geographic Information System) in soil compaction studies by investigating the spectral reflectance in producing soil compaction maps for implementation of precision farming.